Advertisements images and consumption: pedagogical and environmental considerations - Richter, Luciana; Freitag, Vanessa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/2236117010739 This paper discusses the relationship between advertisements images, consumer culture and educational environment. We start from an experience with teachers from public schools, where are discussed the relationship between publicity images and product consumption, and reflected the importance of addressing this issue in the educational context, with a focus on environmental issues. In this sense, the images served as advertising tools to reflect the pedagogical practice of teachers located in São Gabriel - RS. The empirical data of this study were produced through part of a workshop held with 23 teachers in October 2012.